The Solow model in the empirics of growth and trade - Erich Gundlach (Kiel Institute for the World Economy (IfW), 2006)
Translated to a cross-country context, the Solow model (Solow, 1956) predicts that international differences in steady state output per person are due to international differences in technology for a constant capital output ratio. However, most of the cross-country growth literature that refers to the Solow model has employed a specification where steady state differences in output per person are due to international differences in the capital output ratio for a constant level of technology. My empirical results show that the former specification can summarize the data quite well by using a measure of institutional technology and treating the capital output ratio as part of the regression constant. This reinterpretation of the cross-country Solow model provides an interesting implication for empirical studies of international trade. Harrod-neutral technology differences as presumed by the Solow model can explain why countries have different factor intensities and may end up in different cones of specialization.
Keywords: O40; F11; 330; Lerner diagram; Solow Model; Solow-Modell; Wachstumstheorie; Steady-State-Wachstum; Kapitalintensität; Außenwirtschaftstheorie; Internationale Arbeitsteilung; Schätzung; Theorie; Welt